Justice League odyssey. Vol 3. Final frontier - Abnett, Dan (DC Comics, 2020)
"Green Lantern Jessica Cruz leads Justice League Odyssey as guardian of Ghost Sector and fighting their way to defeat the newly empowered, godlike Darkseid. Returned to power, with reborn New Gods at his side and the Ghost Sector as an implacable fortress, Darkseid sets his sights on the remaining universe! Where is Justice League Odyssey? An unknown warrior assembles Green Lantern Jessica Cruz and various heroes to form a new Justice League Odyssey as the guardian of the Ghost Sector, where they're going to have to fight their way through Darkseid's new multi-planet realm of Apokolips to take control of Sepulkore or die trying"--